Beyond the cosmos : what recent discoveries in astrophysics reveal about the glory and love of God - Ross, Hugh (Hugh Norman), 1945- (Orlando, Fla. : Signalman Publishing, 2010)
Ross examines how the discovery of multiple dimensions beyond our own dimensions of space and time explain some of the paradoxes of the Christian faith--from free will and miracles to hell and the Trinity.
An invitation to soar -- Takeoff from ground zero -- Physics breaks through to new realms -- Science's tethers -- Extra dimensions in the Bible -- Extra-dimensional doctrines -- God and extra time dimensions -- Extra-dimensionality and God's proximity -- Extra-dimensionality and God's triunity -- Extra-dimensionality, the incarnation, and the atonement -- Dimensional capacities of created beings -- God's omnipotence v. displayed power -- Extra-dimensionality and the battle of wills -- Extra-dimensionality and salvation's assurance -- Extra-dimensionality and evil and suffering -- God's extra-dimensional love in hell -- Extra-dimensionality and the new creation -- An invitation to soar higher still -- Appendix: Evidence for strings.
Includes bibliographical references and indexes.
Keywords: God (Christianity); Time -- Religious aspects -- Christianity; Astronomy -- Religious aspects; Physics -- Religious aspects -- Christianity; Astronomy -- Religious aspects; God (Christianity); Physics -- Religious aspects -- Christianity; Time -- Religious aspects -- Christianity